SMARTFERTI, SISTEM PAKAR PEMUPUKAN KELAPA SAWIT BERBASIS ANDROID - Erick Firmansyah; Dian Pratama Putra (Jurnal Agroekoteknologi, 2019)
ABSTRACTKnowledge of good fertilization for oil palm on smallholder farmers is still limited.The availability of fertilizer knowledge both from primary sources and in theliterature as a secondary source, does not make it easy for farmers. An expert system is built in the form of a mobile application to implement the available knowledge base to provide fertilizer recommendations. The oil palm fertilization expert system in this research is called SmartFerti. SmartFerti is developed with a reasoning approach using a forward chaining method. The application design is based on the type of nutrients, planting density (stand per hectare, SPH), land area, type of fertilizer, and location. SmartFerti was built using 8 knowledge bases collected from reputable sources which were processed to obtain conclusions. SmartFerti provides fertilizer recommendations which include doses per semester and application time for 11 provinces in Indonesia. Nutrients that can be recommended include nitrogen, phosphorus, potassium, calcium, and magnesium. SmartFerti fertilization expert system uses an android-based interface built using App Inventor 2,0 (www,appinventor,mit,edu).